Colloid, adhesive and release properties of nanoparticular ternary complexes between cationic and anionic polysaccharides and basic proteins like bone morphogenetic protein BMP-2 - Petzold, Ralf; Grab, Anna Luise; Cavalcanti-Adam, Elisabetta A. (Colloids and surfaces. B, Biointerfaces, 2017)
Herein we describe an interfacial local drug delivery system for bone morphogenetic protein 2 (BMP-2) based on coatings of polyelectrolyte complex (PEC) nanoparticles (NP). The application horizon is the functionalization of bone substituting materials (BSM) used for the therapy of systemic bone diseases. Nanoparticular ternary complexes of cationic and anionic polysaccharides and BMP-2 or two further model proteins, respectively, were prepared in dependence of the molar mixing ratio, pH value and of the cationic polysaccharide. As further proteins chymotrypsin (CHY) and papain (PAP) were selected, which served as model proteins for BMP-2 due to similar isoelectric points and molecular weights. As charged polysaccharides ethylenediamine modified cellulose (EDAC) and trimethylammonium modified cellulose (PQ10) were combined with cellulose sulphatesulfate (CS). Mixing diluted cationic and anionic polysaccharide and protein solutions according to a slight either anionic or cationic excess charge colloidal ternary dispersions formed, which were cast onto germanium model substrates by water evaporation. Dynamic light scattering (DLS) demonstrated, that these dispersions were colloidally stable for at least one week. Fourier Transform Infrared (FTIR) showed, that the cast protein loaded PEC NP coatings were irreversibly adhesive at the model substrate in contact to HEPES buffer and solely CHY, PAP and BMP-2 were released within long-term time scale. Advantageously, out of the three proteins BMP-2 showed the smallest initial burst and the slowest release kinetics and around 25% of the initial BMP-2 content were released within 14days. Released BMP-2 showed significant activity in the myoblast cells indicating the ability to regulate the formation of new bone. Therefore, BMP-2 loaded PEC NP are suggested as novel promising tool for the functionalization of BSM used for the therapy of systemic bone diseases.